Mechanical analysis of folding of a tape spring in a flexible hinge design - Goldobin, Nikolay Nikolayevich; Eremin, Nikita Viktorovich (Computational Continuum Mechanics, 2023)
This paper is devoted to the study of flexible tape-spring hinges at the stage preceding the numerical optimization of their geometrical parameters. This stage involves the development of a parametric computational model and a method for conducting complex mechanical analysis of the tape spring. The paper presents a detailed description of the parametric model and the methods for numerical simulation of flexible tape spring hinges using an elastoplastic material model. The capabilities of the methods for nonlinear strength analysis of folded tape springs are illustrated by a few examples of their practical implementation. The stability bounds of the tape spring model are determined by the method of finite element modeling, as well as ways to simplify the calculation model. It has been found that in the numerical simulation of folding stresses, the maximum rotation of the free edge of the tape can be restricted to 30°, at which the stress limit is reached. This makes it possible to reduce the time of the numerical experiment by about 3 times. It is shown that the bilinear model of isotropic hardening of the tape material can be replaced by the linear elastic model, since during the parametric optimization the yield strength is set as a criterion. The use of the linear elastic material model makes it possible to distribute computational resources more effectively. The results of this study will be used in further research for developing a parametric optimization scheme that provides an automated search for the most rational designs of flexible tape-spring hinges.